Exploring the Nexus of Religiosity and Trust in E-commerce: Implications for Purchase Intentions in Pakistan - Siddiqui, Munib; Hameed, Waseem ul (Pakistan Journal of Humanities and Social Sciences, 2023)
This research delved into the influence of religiosity on online shopping, exploring two dimensions: cognitive-based trust rooted in available knowledge and affect-based trust founded on emotional connections. The study considered factors such as ethnicity, education, culture, trust, risk, peer influence, attitude, and more. Notably, there is a scarcity of research in Pakistan on the impact of religion on purchase intention. A qualitative approach was adopted, the paper employs the thematic analysis based on semi-structured interviews, phenomenological technique of reviewing related literature available on e-commerce as well as religiosity, and thematic analysis were done for that number of interviews conducted and recorded. This study lays the foundation for a comprehensive investigation into the integration of Sharia principles within the realm of e-commerce. By examining the current landscape of e-commerce and the challenges faced in ensuring compliance with Sharia principles, this study highlights the critical need for a holistic and integrated approach to address these concerns. The development of relationship between religiosity and purchase intention in Pakistan could be helpful to gain the trust with endorsement of Islamic model of e-commerce. This study could be helpful for the users as well as vendors of the industry.